Racialised Workers and European Older-Age Care From Care Labour to Care Ethics - Sahraoui, Nina (Thinking Gender in Transnational Times,, 2019)
In the context of ageing populations, increasing participation of women in the labour market, growing marketisation of care provision, and, most importantly, global inequalities, racialised care workers have come to fulfil a key role within older-age care in western European societies. This book presents a gendered political economy of migrant and minority ethnic care workers' experiences in older-age care in London, Paris and Madrid. Its cross-national comparative approach allows for a differentiated analysis of the workings of migration, employment and care regimes in three capital cities, with similarly segmented care sectors, yet diverse policies and implications for care workers. Sahraoui provides a novel perspective that advances debates on the ethics of care by foregrounding the voices of racialised care workers and contributing to feminist moral philosophy. Racialised Workers and European Older-Age Care offers unique insights into the meanings of care labour and the challenges arising from processes of neoliberal marketisation, precarisation and institutional racism. The book sketches out an intersectional understanding of the exploitative relationships on which care and social reproduction currently rely and demonstrates why it matters to move care from the margins of society to its centre. This innovative and compelling analysis will appeal to students and scholars of Anthropology, Sociology, Political Science and Social Policy, as well as those working in the interdisciplinary sub-fields of Gender, Migration, Labour, and Racism Studies.